دراسة محدودية تكامل كوشي الشاذ في بعض الصفوف التابعية (Latakia University Journal -Basic Sciences Series, 2017)
درسنا في هذا البحث تكامل كوشي الشاذ لتوابع تنتمي إلى صفوف واسعة من التوابع على أسر شهيرة من المنحنيات وبشكل خاص قمنا بدراسة محدودية هذا التكامل. حصلنا في هذا البحث على بعض النتائج التي تخص تكامل كوشي الشاذ ومحدوديته في صفوف تابعية متفرعة عن فضاء ليبيغ وعلى منحنيات تنتمي إلى أسرة منحنيات كارلسون.In this research westudied singular Cauchy’s integral for functionsbelong to wide classes of functions on a famous curves families .Especially we study the boundness of this integral. Wehave obtained some results about singular Cauchy’s integral and it’sboundness for some functional classes branched from Lebesuge classes.